2016
DOI: 10.21162/pakjas/16.1659
|View full text |Cite
|
Sign up to set email alerts
|

EFFICACY OF RHIZOSPHERIC ORGANISM Rhizobium leguminosarum AGAINST Meloidogyne incognita IN SOYBEAN

Abstract: Present investigation was carried out to assess the biocontrol potential of Rhizobium leguminosarum against root-knot nematode, Meloidogyne incognita on soybean. Effect of Rhizobium strains LSI-21 and CRI-29 was assessed individually and concomitantly on reproduction of M. incognita. In vitro studies were conducted to check the effect of Rhizobium strains on egg hatching and juvenile mortality of M. incognita. Concomitant application of Rhizobium strains was more effective in reducing egg hatching and causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…All isolates gave a positive result for the catalase test, indicating their ability to break down hydrogen peroxide, leading to the release of oxygen bubbles, which is consistent with [28], in their study on Rhizobium bacteria isolated from the roots of nine legume plant species. Most isolates also gave a positive result for the oxidase test, which is consistent with , [29] in their study on Rhizobium leguminosarum bacteria in soybean plants. Most isolates gave a negative result for the indole test, which is consistent with, [30] in their Identification of B.japonicum bacteria isolated from soybean and cowpea plants.…”
Section: Resultssupporting
confidence: 88%
“…All isolates gave a positive result for the catalase test, indicating their ability to break down hydrogen peroxide, leading to the release of oxygen bubbles, which is consistent with [28], in their study on Rhizobium bacteria isolated from the roots of nine legume plant species. Most isolates also gave a positive result for the oxidase test, which is consistent with , [29] in their study on Rhizobium leguminosarum bacteria in soybean plants. Most isolates gave a negative result for the indole test, which is consistent with, [30] in their Identification of B.japonicum bacteria isolated from soybean and cowpea plants.…”
Section: Resultssupporting
confidence: 88%
“…Published data of comparisons between the efficiency and feasibility of inoculation of PBM via seed coating and other methods are still scarce. In a greenhouse experiment, after comparing seed coating of Rhizobium strains with soil drench application for the management of root-knot nematode Meloidogyne incognita on soybean, Ahmed et al (2016a) found that seed dressing was more effective in controlling the reproduction of M. incognita and increasing plant height, and fresh and dry root and shoot weight. In a trial using maize, Rocha et al (2019a) compared the delivery efficiency of R. irregularis via soil inoculation (4860 AM fungal propagules per plant) with seed coating (273 AM fungal propagules per seed) under greenhouse conditions.…”
Section: Seed Coating With Beneficial Microbesmentioning
confidence: 99%
“…As a result, attempts to elucidate the ecological (allelopathic, phytotoxic, anti-microbial) implications and direct/indirect roles of phenolic acids in the rhizosphere can be very challenging. Notably, various phenolic acids which are secreted as root exudates [ 59 , 74 ] can be readily metabolized by various soil microorganisms (bacteria, fungi) and, consequently, their presence can alter the diversity and composition of soil microbial communities resulting in the establishment of pathogenic or mutualistic interactions [ 29 , 75 , 76 , 77 , 78 ]. In soybeans for instance, various phenolic acids, such as benzoic acids, are exudated into the rhizosphere and can act as chemoattractants that facilitate quorum sensing activities in beneficial microbes, such as Rhizobium [ 70 ], which subsequently help protect against nematode infection ( M. incognita ) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, various phenolic acids which are secreted as root exudates [ 59 , 74 ] can be readily metabolized by various soil microorganisms (bacteria, fungi) and, consequently, their presence can alter the diversity and composition of soil microbial communities resulting in the establishment of pathogenic or mutualistic interactions [ 29 , 75 , 76 , 77 , 78 ]. In soybeans for instance, various phenolic acids, such as benzoic acids, are exudated into the rhizosphere and can act as chemoattractants that facilitate quorum sensing activities in beneficial microbes, such as Rhizobium [ 70 ], which subsequently help protect against nematode infection ( M. incognita ) [ 29 ]. Although these findings suggest phenolic acids may positively impact soybean–SCN interactions, there is very little evidence surrounding their physical/chemical interactions under highly variable field conditions to assess their agricultural implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation